Implications of non‐coding RNAs in viral infections. (12th July 2016) - Sharma, Nikhil; Singh, Sunit K.
Summary: The advances in RNA sequencing have unveiled various non‐coding RNAs (ncRNAs), which modulate the gene expression. ncRNAs do not get translated into proteins. These include transfer RNAs, ribosomal RNAs, microRNA (miRNA), short interfering RNA, long non‐coding RNA, piwi‐interacting RNA and small nuclear RNA. ncRNAs regulate gene expression at various levels and control cellular machinery. miRNAs have been reported in plants, animals, several invertebrates and viruses. The miRNAs regulate the gene expression post‐transcriptionally. Viral infection strongly influences the abundance and the distribution of miRNAs and other ncRNAs within the host cells. Viruses may encode their own miRNA, which help in the viral life cycle and other aspects of pathogenesis. Viruses are known to successfully modulate the expression pattern of ncRNAs. The ncRNA‐based strategies adopted by viruses for their survival present a complex picture of host–virus interactions. Copyright © 2016 John Wiley & Sons, Ltd.